Seniors’ Needs and Dreams as Factors of Successful Aging - Rejter, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The aim of the research was to present the dreams of seniors on the basis of field research. Thanks to the obtained research material, based on the case study method, the needs and dreams of the elderly were diagnosed. The research results obtained in this way allow to identify activities leading to their meeting needs.